(untitled) (Quinto Sol, 2023)
This article analyzes groundbreaking innovation processes on sheep farming which took place in the Rio de la Plata region at the same time as in other important world productive areas (Australia, the United States). The new technology embraced the multiple dimensions of the productive process, in order to successfully support the crossbreeding between the creole sheep and imported rams of top quality wool. A new periodization is proposed, from the outset to the moment preceding the highest wool export boom in 1853. The transformations which took place between the end of the 18th and the mid of the 19th Century have consequently been assessed.